Persepsi mahasiswa akuntansi terhadap minat profesi akuntan pendidik: teori motivasi dan harapan berbasis akuntansi syariah - Hosnan, Ali; Leniwati, Driana; Wahyuni, Endang Dwi; Mudrifah, Mudrifah (LPMP Imperium, 2023)
Accountant educators have a significant role in developing human resources now and in the future because accountant educators are the starting point in creating professional accountants who behave ethically. The purpose of this study is to analyze how accounting students perceive the interest of the accounting profession as educators based on Herzberg's Hygiene-Motivation Theory and Vroom's Expectancy Theory. Data were obtained from interviews with research subjects, accounting lecturers, and students at the University of Muhammadiyah Malang, Class of 2018 and 2019. Based on Herzberg's Motivation Theory, factors that influenced students' disinterest in the accounting educator field were job interest, company policy, working conditions, and salary levels in expectancy theory. Students are more likely to expect to become accountants in companies and governments when they graduate from accounting majors.